Inter- district Healthcare facilities in Assam; An Evidence from Secondary Sources (International Journal of Food and Nutritional Sciences, 2022)
The paper has given a brief discussion on health status of Assam. Further, it has also provided an outline in distribution of public healthcare facilities across districts of Assam. The health status is indicated by the maternal mortality ratio and infant mortality rate. Both the indicators are considered essential subjects for the global community and uses as an indicator to compare health status across countries. Moreover, these indicators are also used to reflect the socio-economic development process of a country.